Dispositivos sensores em fibra para uso em refratometria - Kamikawachi, Ricardo Canute (2007)
This work describes the production and characterization of long period gratings (LPG) and etched fiber Bragg gratings as sensors. Both the production and characterization were carried out at the Laser Laboratory of UTFPR and the production and characterization of etched fiber Bragg gratings were carried out at Coherent Optics Laboratory of University of Aveiro, Portugal. Aspects concerning to the production and operation principles are shown. The results obtained from the grating production and characterization, as well as the experimental set-up developed to these goals are presented. The method used to write the gratings was the application of point-to-point electrical arch discharge, resulting in grating periods of 598 and 600 μm operating at the third window transmission around 1.55 μm. The long period gratings and the etched fiber Bragg gratings were characterized as a function of modification on the refractive index of the external surrounding environment, of temperature changes and strain (this last parameter was carried out only for long period gratings), the cross sensitivity also was characterized. The refractive index response of long period grating at two different conditions, one of them for presence of gasoline blend in water environment and another one for vapors of some hydrocarbon in closed container, points to the use of this device for hydrocarbon leakage detection at refineries and gas stations. Long period gratings e results obtained for ethanol agrees with the data find in literature, showing that this is a good technique for this goal.